Congenital Fiber Type Disproportion Genetics - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Novel heterogeneous missense mutations in five families with congenital fiber type disproportion (CFTD) were identified in a study at Children's Hospital at Westmead, University of Sydney, and other centers in Australia, Canada, and France.